Legal Review of Sharia Transactions in Modern Economics - Fauziah Zulfa Nur Laila; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In the era of rapid technological development and globalization, the modern economy presents new challenges in terms of transactions following sharia economic principles. Islam, as a timeless universal religion that regulates faith, sharia and morals comprehensively, exists as a guide for every Muslim in carrying out business transaction activities. Transaction comes from the English